A validation study of the State Self-Esteem Scale-20 (SSES-20) and the State Self-Esteem Scale-6 (SSES-6) in a Spanish-speaking sample - Escrivá-Martínez, Tamara; Molinari, Guadalupe; Ciudad-Fernández, Víctor; Corno, Giulia; Baños, Rosa (Anales de Psicología / Annals of Psychology, 2024)
The State Self-Esteem Scale has not been studied in the Spanish population yet. Our objective was to assess the factor structure and internal consistency of the State Self-Esteem Scale (SSES-20 and SSES-6) in a Spanish-speaking sample. The second objective was to determine its convergent and discriminant validity by examining its relationships with variables such as trait self-esteem, social desirability, depression, and anxiety. The sample consisted of 713 Spaniards (77.2% female; Mean Age = 25.32 years). Findings suggest that a bifactor model with a general factor and three subdimensions provided a better fit for SSES-20 data. For the SSES-6 version, a hierarchical model with three non-correlated first-order factors and a common hierarchical factor was found to be the best fit. All dimensions exhibited moderate to excellent reliability. All factors were positively linked to trait self-esteem and social desirability, while inversely related to depression and state anxiety. Finally, performance, appearance, and social state self-esteem dimensions from SSES-20 negatively predicted depression and state anxiety using linear regression models. Both Spanish versions, SSES-20 and SSES-6, demonstrated adequate psychometric properties within this sample, suggesting potential generalizability to diverse Spanish populations.